(untitled) (Cadernos de Sociomuseologia, 2021)
This article aims to conduct an analysis of the use of co-design methodologies in accessibility projects for the visually impaired in museums. The article presents a discussion of the practices of participatory methodologies in museum projects, in particular the co-design approach. It proceeds with a comparative case study, analyzing articles that describe the implementation of co-design projects in museum and educational contexts. The purpose of this comparative study is to present different methods of co-design, what goals can be achieved by these methodologies and to analyze and compare the results and challenges found. The authors selected four co-design projects for this comparative study, analyzing their differences and similarities. The conclusion of this analysis is that participatory projects bring as a benefit not only the creation of new audiences, but the enrichment of the museum object itself, promoting new forms of enjoyment and acquisition of knowledge. This article aims to contribute to the development of future studies and projects on accessibility that may represent better